Design of an axial mode helical antenna with buffer layer for underwater applications - Afiza Nur Jaafar; Hajar Ja’afar; Yoshihide Yamada; Fatemeh Sadeghikia; Idnin Pasya Ibrahim; Mohd Khairil Adzhar Mahmood (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Recently, there is an increasing demand for high-speed wireless communication network for short-range underwater communication. From previous research, most underwater antennas produced omnidirectional radiation pattern which has lower antenna gain. There are a few considerations that need to be taken if the antenna is designed to operate in water environment. This paper discusses the electromagnetic properties which affect the underwater antenna design. Physical properties such as electrical permittivity and conductivity of water contribute significant effect to the size of the antenna as it influences the behavior of electromagnetic signal that propagates in water. In this study, an axial mode helical antenna with waterproof container is presented which operates at 433 MHz. The axial mode helical antenna has circular polarization and is suitable to support wireless application which is surrounded by some obstruction. The proposed antenna produces a bidirectional radiation pattern by placing it into a waterproof casing. Good agreement between the simulation and measurement results validates the concept. However, a little discrepancy between the simulated and measured results may be attributed to the noise originated from the equipment and the environment.